MENINGKATKAN KUALITAS HIDUP PEMULUNG DI BANTAR GEBANG DENGAN PENDEKATAN KAMPUNG TUMBUH - Grisvian Gilchrist Agustin; F. Tatang H. Pangestu (Jurusan Arsitektur dan Perencanaan, 2023)
Bantar Gebang TPST will soon be full with the remaining 10 million tons of capacity from 49 million tons. This has led to a high hill of garbage in Bantar Gebang. The effect of this pile of garbage has an impact on the surrounding community and scavengers. Air and water pollution occurs around the Bantar Gebang TPST. The impact of this pollution makes the quality of life around Bantar Gebang decline. Mountains of trash located in several zones will be rearranged into green open spaces. The scavengers' housing in Bantar Gebang uses materials such as zinc, cloth and wood that are not suitable, causing problems with comfort. In addition, the residential area of ​​the scavengers is in an unhealthy area, so that Architecture can improve the quality of life for scavengers in Bantar Gebang by exploiting the potential that exists in Bantar Gebang. Improve the occupancy of scavengers in Bantar Gebang and appreciate the expertise of scavengers to improve the quality of life for scavengers in Bantar Gebang. The method used is a survey and literature review of the condition of scavengers and the environment in Bantar Gebang. With the pattern of arranging the scavengers' dwellings that extend in a direction perpendicular to the road, the area can be used as a place for waste sorting to be carried out by his wife and family. Thus the designed architectural solution is a 2x2 meter module system with a knock down system. With a module system that increases flexibility for the possibility of growing a scavenger village. Keywords: knockdown; pollution; quality; TPST Abstrak TPST Bantar Gebang akan segera penuh dengan sisa kapasitas 10 juta ton dari 49 juta ton. Hal ini telah menyebabkan tingginya bukit sampah di Bantar Gebang. Efek dari tumpukan sampah ini ternyata berdampak ke masyarakat sekitar dan para pemulung. Pencemaran udara dan air terjadi di sekitaran TPST Bantar Gebang. Dampak dari pencemaran ini membuat kualitas hidup di sekitar Bantar Gebang menurun. Gunung sampah yang berada di beberapa zona akan ditata kembali menjadi ruang terbuka hijau. Hunian para pemulung yang berada di Bantar Gebang menggunakan bahan-bahan seperti seng, kain dan kayu yang kurang layak sehingga menimbulkan permasalahan terhadap kenyamanan. Selain itu area hunian para pemulung ini berada di daerah yang kurang sehat, sehingga Arsitektur dapat meningkatkan kualitas hidup para pemulung di Bantar Gebang dengan memanfaatkan potensi yang ada di Bantar Gebang. Meningkatkan hunian para pemulung di Bantar Gebang dan menghargai keahlian para pemulung untuk meningkatkan kualitas hidup para pemulung di Bantar Gebang. Metode yang digunakan adalah survey dan tinjauan literatur terhadap kondisi pemulung dan lingkungan di Bantar Gebang. Dengan pola penyusunan hunian para pemulung yang memanjang dengan arah tegak lurus dengan jalan, area tersebut dapat digunakan sebagai tempat pemilahan sampah yang dikerjakan oleh istri dan keluarganya. Dengan demikian solusi arsitektur yang dirancang berupa sistem modul 2x2 meter dengan sistem knockdown. Dengan sistem modul sehingga meningkatkan fleksibilitas untuk kemungkinan tumbuhnya sebuah kampung pemulung.